EFFECT OF SEASON ON BIOCHEMICAL CONSTITUENTS OF SERUM IN COMMERCIAL BROILER CHICKEN - Devi, T.G; Samanta, A.K; Samanta, r.; Barma, N. Deb (Indian Journal of Animal Production and Management, 2017)
A study was conducted on broilers in two trials to estimate blood biochemicalparameters during summer and winter season. Blood samples (32 nos) were collected fromtwo birds (one male & one female) per replicate, before slaughtering. The result revealedthat the glucose concentration was significantly (p